Benefits of mushroom polysaccharides use in functional food production - Sokot, O. E. (ТДАТУ, 2021)
The result was following: waffles had a slightly bright color and characteristic mushroom flavor. Organoleptic analysis showed that the use of mushroom powder is a rather promising way to develop functional products.
Keywords: fast food; waffles with mushroom powder; polysaccharides of fungi